Ethanol-Mediated Regulation of Cytochrome P450 2A6 Expression in Monocytes: Role of Oxidative Stress-Mediated PKC/MEK/Nrf2 Pathway - Jin, Mengyao (Public Library of Science, 2012)
Cytochrome P450 2A6 (CYP2A6) is known to metabolize nicotine, the major constituent of tobacco, leading to the production of toxic metabolites and induction of oxidative stress that result in liver damage and lung cancer. Recently, we have shown that CYP2A6 is induced by ethanol and metabolizes nicotine into cotinine and other metabolites leading to generation of reactive oxygen species (ROS) in U937 monocytes. However, the mechanism by which CYP2A6 is induced by ethanol is unknown. In this study, we have examined the role of the PKC/Nrf2 pathway (protein kinase C-mediated phosphorylation and translocation of nuclear erythroid 2-related factor 2 to the nucleus) in ethanol-mediated CYP2A6 induction. Our results showed that 100 mM ethanol significantly induced CYP2A6 mRNA and protein (∼150%) and increased ROS formation, and induction of gene expression and ROS were both completely blocked by treatment with either a CYP2E1 inhibitor (diallyl sulfide) or an antioxidant (vitamin C). The results suggest the role of oxidative stress in the regulation of CYP2A6 expression. Subsequently, we investigated the role of Nrf2 pathway in oxidative stress-mediated regulation of CYP2A6 expression in U937 monocytes. Our results showed that butylated hydroxyanisole, a stabilizer of nuclear Nrf2, increased CYP2A6 levels >200%. Staurosporine, an inhibitor of PKC, completely abolished ethanol-induced CYP2A6 expression. Furthermore, our results showed that a specific inhibitor of mitogen-activated protein kinase kinase (MEK) (U0126) completely abolished ethanol-mediated CYP2A6 induction and Nrf2 translocation. Overall, these results suggest that CYP2E1-mediated oxidative stress produced as a result of ethanol metabolism translocates Nrf2 into the nucleus through PKC/MEK pathway, resulting in the induction of CYP2A6 in monocytes. An increased level of CYP2A6 in monocytes is expected to further increase oxidative stress in smokers through CYP2A6-mediated nicotine metabolism. Thus, this study has clinical relevance because of the high incidence of alcohol use among smokers, especially in HIV-infected individuals.